2018
DOI: 10.1080/23802359.2018.1431074
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequence of Rosa roxburghii and its phylogenetic analysis

Abstract: Rosa roxburghii Tratt. is a famous Chinese traditional medicine with long history, here we characterized the whole chloroplast (cp) genome sequence of R. roxburghii by Illumina pair-end sequencing. The complete cp genome was 156,749 bp in length, containing a large single copy (LSC) region of 85,862 bp and a small single copy (SSC) region of 18,791 bp, which were separated by a pair of 26,053 bp inverted repeat regions (IRs). The genome contained 139 genes, including 88 protein-coding genes (82 PCG species), 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Protein coding genes and ribosomal RNA (rRNA) genes were primarily identified using DOGMA (Dual Organellar GenoMe Annotator) [20], and transfer RNA (tRNA) genes were identified using tRNAscan-SE 2.0 [21]. Further annotations were identified by comparing chloroplast genomes with the well-defined Nicotiana tabacum chloroplast genome (Z00044) [22] and Rosa roxburghii chloroplast genome (NC_032038) [23] from GenBank as references. Finally, all gene annotations were verified and accurately adjusted via BLASTN and BLASTX searches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein coding genes and ribosomal RNA (rRNA) genes were primarily identified using DOGMA (Dual Organellar GenoMe Annotator) [20], and transfer RNA (tRNA) genes were identified using tRNAscan-SE 2.0 [21]. Further annotations were identified by comparing chloroplast genomes with the well-defined Nicotiana tabacum chloroplast genome (Z00044) [22] and Rosa roxburghii chloroplast genome (NC_032038) [23] from GenBank as references. Finally, all gene annotations were verified and accurately adjusted via BLASTN and BLASTX searches.…”
Section: Methodsmentioning
confidence: 99%
“…The complete chloroplast genomes of R. multiflora , R. luciae , and R. maximowicziana from this study and chloroplast genomes of two other Rosa species from other infrageneric groups in GenBank, Rosa roxburghii (subgenus Platyrhodon ; NC_032038) [23] and Rosa odorata var. gigantea (subgenus Rosa section Chinenses ; KF753637) [25], were compared using mVISTA [26,27] with LAGAN alignment program [28].…”
Section: Methodsmentioning
confidence: 99%
“…However, to date, only a few cp genomes of Rosa spp. have been published in the GeneBank database [32][33][34][35] , which is a source of data on sequence diversity. Furthermore, few studies have focused on molecular markers from the cp genome of roses.…”
mentioning
confidence: 99%
“…In recent years, it was widely applied in food and cosmetics for its nutritional and health benefits ( Yang et al, 2020 ). Its root, leaf, and fruit have been used as traditional medicinal materials in the treatment of several diseases, including strengthening the spleen, dyspepsia, enteritis, and scurvy ( Wang et al, 2018 ). Modern pharmacological studies have demonstrated that some components of R. roxburghii exhibited several biological activities, such as excellent hypoglycemic and hypolipidemic effects, enhancing immunity, antioxidation, and anti-tumor activities ( Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%